Training zones estimation - Goldschmidt, Tobiáš; Janoušek, Oto (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2024)
Training zones, or exercise intensity zones, are a vital part of modern sport. Assessing these zones is not only costly but also needs to be done quite frequently. This paper proposes a new way of assessing training zones to overcome these challenges - based on DFA alpha1. It shows that laboratory assessment of training zones by DFA alpha1 is quite accurate. However, its usage to monitor exercise intensity in daily use is not as accurate, especially during low and medium intensity exercises.
Keywords: detrended fluctation analysis; heart rate variability; training zones